Geochemical and Sedimentological Investigation of Possible Devonian-Mississippian Glaciation in the Appalachian Basin, Pennsylvania - Vollhardt, Heather; Fedorchuk, Nicholas; Morales, Ivianna; Cordie, David; Regan, Eric (Joint 72nd Annual Southeastern/ 58th Annual Northeastern Section Meeting - 2023, 2023)
The Late Paleozoic Ice Age (LPIA) was the last major icehouse climate (low CO2,...
Keywords: dept.esc

As geleiras carboníferas no sul do Brasil - da Rosa, Eduardo; Vesely, Fernando Farias; Isbell, John L.; Fedorchuk, Nicholas D. (Boletim Paranaense de Geociências, 2021)
The Late Paleozoic Ice Age (LPIA; 362 to 256 Ma) left a record in the Gondwanan sedimentary basins as glacial successions and ice-carved features. In the Paraná Basin, the glaciation is recorded in the Itararé Group and on its basal unconformity that contains micro to mega scale erosive features. Diamictites and glacial erosive landforms such as striated surfaces have been used to reconstruct past glacial dynamics as well as to define ice kinematics and ice-spreading centers. However, soft-sediment striated surfaces generated by scouring of iceberg keels are also common in the Itararé Group strata as well as diamictites generated by nonglacial processes. Assemblages of erosive landforms left behind by Carboniferous glaciers in southern Brazil are evidence for different glaciation scenarios. In the Paraná State, flat-based, unconfined ice lobes advanced northward over Devonian sandstones of the Furnas Formation. In the Santa Catarina state, the glacial advances are characterized by an irregular topography on igneous and metamorphic basement, probably a result of advancing ice streams. In Rio Grande do Sul, an assemblage of paleovalleys is interpreted as the product of glaciation; however, these valleys could have been generated by tectonism and not by glacial erosion. The complex glacial events that took place in southern Brazil are being better understood due to detailed studies on the record left behind by Carboniferous glaciers. © 2021 Universidade Federal do Parana. All rights reserved.
Keywords: Carboniferous; Parana Basin; dept.esc; diamictite; erosion; glaciation; glacier; ice stream; peer-reviewed; subglacial deposit

Assessing the risk of contaminated sediments during small dam removal projects in the Long Island Sound watershed - Alix, Katelyn; Fedorchuk, Nicholas; Breslin, Vincent; Hoehne, Gary; Hayton, Jam; Balbachan, Kayla (Geological Society of America, 2025)
Keywords: Computer science; Contamination; Ecology; Environmental science; Geology; Geotechnical engineering; Hydrology (agriculture); Oceanography; Sound (geography); Watershed; dept.egm; dept.esc

Gravitational resedimentation as a fundamental process in filling fjords: Lessons from outcrops from a late Palaeozoic fjord in Namibia - Menozzo da Rosa, Eduardo; Isbell, John L.; McNall, Natalie; Fedorchuk, Nicholas; Swart, Roger (Sedimentology, 2023)
The stratigraphic architecture of fjords is complicated due to the delicate interplay between ice dynamics, sediment supply, relative sea-level fluctuations and slope failures. Glaciogenic sediment is prone to failure and to be carried downslope to the fjord floor through the entire spectrum of mass movements and subaqueous density flows, as the unstable paraglacial submarine landscape moves towards stability. Palaeofjords formed by Gondwanan glaciers during the late Palaeozoic Ice Age contain a compelling record of gravitational resedimentation in fjord depositional systems. This paper showcases the geomorphology and depositional history of a glacial cycle in the Orutanda fjord in north-western Namibia as an example of an overdeepened fjord basin fill dominated by products of subaqueous gravitational processes. During glaciation, the Orutanda glacier carved a 20 km long by 3.7 km wide glacial trough that embodies an overdeepened basin. Ice thickness during terminal glacial occupation of the fjord is estimated to had been up to 200 m based on the fjord geomorphology. The progressive retreat of the tidewater glacier, concomitant with marine flooding, increased accommodation space in the overdeepened basin during deglaciation. During this stage, proglacial sedimentation through iceberg rafting and settling of turbid plumes was outpaced by intense paraglacial downslope resedimentation of glacially-transported debris. Successive failures from the fjord walls and downslope resedimentation resulted in coalescing debrite–turbidite lobes on the fjord floor. Slide deposits, composed entirely of deformed debrites and turbidites, indicate that these resedimented facies were prone to renewed mass wasting. As the Orutanda glacier melted, the fjord experienced the axial progradation of a fjord-head delta registered only by turbidites and slide deposits derived from its collapse. The Orutanda fjord sheds light on the relevance of paraglacial mass wasting in overprinting glaciogenic deposits. This insight is key to understanding the role of glaciers versus non-glacial processes in producing the glacial deep-time record.
Keywords: Debris flows; Dwyka Group; dept.esc; late Palaeozoic Ice Age; mass wasting; paraglacial processes; peer-reviewed; turbidites

Reappraisal of Exceptionally Preserved S-Forms, Striae, and Fractures from Late Paleozoic Subglacial Surfaces in Paleofjords, NW Namibia - Fedorchuk, Nicholas D.; Isbell, John L.; Rosa, Eduardo L. M.; Swart, Roger; McNall, Natalie B. (Sedimentary Geology, 2023)
Determining the grounded ice dynamics of deep-time glaciations is limited by the scarcity of well-preserved subglacial erosional features and their irregular distribution. In particular, small-scale erosional features known as s-forms that are subglacially sculpted in bedrock by water and/or ice are rarely preserved from the pre-Cenozoic record. A detailed re-examination of two late Paleozoic (late Carboniferous–early Permian) glacially-polished, surfaces at the base of the Dwyka Gp. within paleofjords located in the Kaokoveld region of northwest Namibia reveals a range of erosional features including: complex, multi-directional striae that crosscut each other, crescentic markings, chattermark trails, sinuous furrows, linear furrows, transverse troughs, comma forms, sichelwannen, muschelbrüche, cavettos, a pothole, and rock drumlins. The first study location in the Sanitatis paleovalley is previously undescribed and consists of striae and fractures on a polished granite bedrock surface located on the paleovalley floor. Striae, crescentic markings, and chattermark trails indicate ice movement to the west/northwest (striae mean azimuth of 276°). The second location in the Hoarusib paleovalley was previously described and is located on a multi-level, resistant, quartzite bedrock ridge close to or on the valley wall. This location contains numerous s-forms, striae, and fractures, as well as onlapping glaciogenic sediments, including diamictite plastered within a pothole. Some of these features are superimposed on rock drumlins. These erosional features were likely formed by a combination of pressurized subglacial meltwater and glacial abrasion underneath a glacier as it flowed over and around a resistant bedrock outcrop. Orientations of striae and chattermark trails at the second location indicate a primary direction of ice movement toward the west/northwest (striae modal azimuth of 275°), a minor secondary movement to the southwest (255°), and abundant third-order striae indicating ice flow around bedrock obstacles. However, cross-cutting relations suggest the primary and secondary striae orientations are not related to two distinct glacial advances as previously thought. The complex relationships between striae, fractures, and s-forms suggest that a combination of pressure melting, abundant subglacial meltwater, debris-rich basal ice, and variable ice flow paths around resistant obstacles was required to form these features. We conclude that the study locations were overridden by relatively thick (>210 m) warm-based or polythermal glaciers that were confined to a network of fjords as ice receded and stagnated. The glaciers flowed west into present-day Brazil during the late Paleozoic and likely overtopped the paleovalley walls during times of ice maxima.
Keywords: Carboniferous; Dwyka; Erosional; Fjords; Glacial; Permian; dept.esc; peer-reviewed

Reassessing a glacial landscape developed during terminal glaciation of the Late Paleozoic Ice Age in Uruguay - Isbell, John L.; Fedorchuk, Nicholas D.; Rosa, Eduardo L. M.; Goso, César; Alonso-Muruaga, Pablo J. (Sedimentary Geology, 2023)
Whalebacks, roche moutonnées, and S-forms carved on Ediacaran granitoids near Cerro de las Cuentas, Uruguay, along with overlying diamictites, siltstones, and sandstones displaying soft-sediment grooved and striated surfaces in the Pennsylvanian San Gregorio Formation, record the glacial to post-glacial transition in the linked Norte, southern Paraná and Chaco-Paraná basins of Uruguay, Brazil, and Argentina respectively. Early authors reported these features resulted from subglacial abrasion and deposition as lodgement tills and glaciotectonites. Our re-examination reveals a nuanced setting with changing ice thicknesses, subglacial kinematics, and ice proximal glaciomarine dynamics associated with advance and retreat of an ice stream, or multiple advances of the Uruguayan Ice lobe, during glaciation of the Late Paleozoic Ice Age (LPIA) in these basins. The preserved landforms indicate temperate glacial conditions. Whalebacks formed under 1.6 to 2.5 km-thick ice and likely formed when the lobe extended across the Uruguayan and Rio Grande do Sul shields into the adjacent Paraná Basin. Previously unidentified m-scale roches moutonnées cut into one whaleback developed under thinner ice where reduced basal pressure allowed for the opening of air and water-filled cavities, thus facilitating quarrying on the lee side of basement bumps. S-forms provide additional evidence for the occurrence of subglacial waters, indicating that the basal ice was at or above its pressure melting point. The lower meter of the overlying strata consists of interstratified trace fossil-bearing, laminated siltstones; thin-bedded diamictites; and current-rippled sandstones. Trace fossils belonging to the Mermia ichnofacies within the basal siltstones, as well as acritarchs in the overlying siltstones, suggest that these sediments were deposited in ice-proximal subaqueous settings with contributions from meltwater discharge. Graded siltstone laminae suggest settling from suspension likely from meltwater plumes, while thin-bedded diamictites were deposited either as debris flows or as two-component sedimentation with fines settling from suspension and coarser particles introduce as iceberg-rafted dropstones. Current-rippled sandstones indicate the occurrence of underflow currents. Soft-sediment troughs, grooves, and striations cutting these sediments display curved and sinuous paths with some features oriented perpendicular, and one oriented opposite to the overall trend. They contain marginal and terminal berms typical of iceberg scour marks suggesting transit across the area by icebergs calving from a tidewater ice front located to the SE.
Keywords: Iceberg keel marks; Late Paleozoic Ice Age; Roche moutonnées; San Gregorio Fm; Uruguayan Ice Lobe; Whalebacks; dept.esc

Glacial and postglacial interpretation of Late Paleozoic sedimentation in a tectonically active mountain front in Paganzo Basin, Argentina - Colombi, Carina; Alonso-Muruaga, Pablo; Kusick, Allison; Isbell, John; Fedorchuk, Nicholas; Alarcón, Carlos; Limarino, Carlos (Journal of Palaeogeography, 2025)
The Guandacol Formation corresponds to glacial episode 4 of the "Late Paleozoic Ice Age" in western Gondwana. It represents the final glaciation of westernmost Gondwana and the beginning of deglaciation that swept across the supercontinent throughout the rest of the Paleozoic. A succession of transitional sedimentary facies associations characterizes the eastern outcrops of the Guandacol Formation. These facies associations are interlayered with several deposits of mass-transport complexes (MTC) and present the occasional opportunity to conduct a deep-time analysis of the effect of tectonism in what is interpreted to be glacially-influenced deposits. Six sedimentary facies associations were recognized in the lower part of the Guandacol Formation. Facies association 1 (interbedded diamictites, sandstones, and mudstones) overlies MTC 1 and is interpreted as sedimentation into a marine glacially-influenced outwash fan. Facies association 2 (ponded interbedded sandstones, mudstones, and diamictites) was deposited as subaqueous underflows/turbidites and debris flows covering the irregular paleotopography of MTC 2. Facies association 3 (white medium- to coarse-grained sandstones and conglomerates) represents a small deltaic system. Facies association 4 (rhythmites with dropstones and sandstones) was deposited in a partially ponded water body resulting from the collapse and paleotopography of MTC 3. Facies association 5 (coarsening-upward cycles of mudstones and sandstones) was deposited in prodelta to delta front environments. Finally, facies association 6 (conglomerates, sandstones, and mudstones) corresponds to the subaerial deltaic platform. The evolution of depositional environments suggests three glacially-linked stages: Stage 1 — Initial retreat of the nearby ice masses (facies association 1); Stage 2 — Further retreat of glaciers and the progressive decoupling between ice masses and sea (facies associations 2 and 3); and Stage 3 — Postglacial sedimentation dominated by deltaic progradation during highstand conditions (facies associations 4 to 6). The importance of the paleogeographic context is emphasized in which the tectonism triggered recurrent events of MTC that continually modified the topography and sedimentary patterns, interrupting and complicating the stratigraphy of the interpreted glacial and postglacial sedimentation.
Keywords: Diamictites; Front (military); Geology; Geomorphology; Glacial period; Mass transport complex; Oceanography; Paleontology; Paleozoic; Postglacial sedimentation; Sediment; Sedimentation; Structural basin; Tectonism; dept.esc; peer-reviewed

Provenance of late paleozoic glacial/post-glacial deposits in the eastern chaco-paraná basin, uruguay and southernmost paraná basin, brazil - Fedorchuk, Nicholas D.; Griffis, Neil; Isbell, John L.; Goso, César; Rosa, Eduardo L.M.; Montañez, Isabel P.; Yin, Qing-Zhu; Huyskens, Magdalena H.; Sanborn, Matthew E.; Mundil, Roland; Vesely, Fernando Farias; Iannuzzi, Roberto (Journal of South American Earth Sciences, 2021)
The Paraná Basin, Brazil and the Chaco-Paraná Basin, Uruguay both contain sedimentary records that are critical to reconstructing late Paleozoic ice centers in central Gondwana. The orientations of subglacial landforms and glaciotectonic structures suggest that late Paleozoic glacial deposits in the eastern Chaco-Paraná Basin and the southernmost Paraná Basin are genetically related, as they were likely glaciated by the same ice center. However, the location and extent of the ice center responsible for depositing these sediments are unclear. Furthermore, changes in sediment dispersal patterns between glacial, inter-glacial, and post-glacial intervals are not understood for this region of Gondwana. Therefore, this study utilized U–Pb detrital zircon geochronology to assess the provenance of glacial and post-glacial sediments from the eastern Chaco-Paraná Basin (San Gregorio, Cerro Pelado, Tres Islas Formations) and the southernmost Paraná Basin (Itararé Group). Results show dominant age peaks at 520–555 Ma, 625 Ma, 750–780 Ma, and 900–1000 Ma in all samples from the eastern Chaco-Paraná Basin. These zircons are interpreted to have been derived from sources in the Cuchilla Dionisio Terrane and Punta del Este Terrane in southeastern Uruguay, and possibly the Namaqua Belt in southern Namibia. Another important source was likely Devonian sedimentary rocks of the Durazno Group in central/eastern Uruguay. Meanwhile, a sample of the glaciogenic Itararé Group from the southernmost Paraná Basin contains a different detrital zircon signature with peaks at 580 Ma, 780 Ma, 2110 Ma, and 2500 Ma that closely resembles underlying sedimentary and meta-sedimentary rocks of the Precambrian/Cambrian Camaquã Basin. Detrital zircon ages in the glacial and post-glacial sediments indicate that local sources were dominant. In contrast, zircon ages from relatively ice-distal glaciomarine intervals in the Chaco-Paraná Basin reflect more distal sources to the east and southeast, which indicates a larger drainage catchment opened when glaciers retreated and/or the zone of maximum subglacial erosion shifted. Although most zircon ages in the Chaco-Paraná Basin can be attributed to Uruguayan sources, results support the hypothesis that glaciers emanated from southern Namibia and southeast Uruguay into the Chaco-Paraná Basin. From there, ice flowed northwest into the Paraná Basin and then receded back towards Africa as the paleoclimate warmed. The detrital zircon inventory in our study region is distinct from the eastern Paraná Basin, suggesting at least two unique African source regions for glaciers that deposited sediments in the Paraná and Chaco-Paraná Basins. © 2020 Elsevier Ltd
Keywords: Brazil; Carboniferous; Chaco Basin; Paleozoic; Parana Basin; Uruguay; dept.esc; geochronology; glacial deposit; glacial landform; peer-reviewed; provenance; sediment transport; sedimentary rock; subglacial environment; uranium-lead dating; zircon

Evaluation of physical and chemical proxies used to interpret past glaciations with a focus on the late Paleozoic Ice Age - Isbell, John L.; Vesely, Fernando Farias; Rosa, Eduardo L.M.; Pauls, Kathryn N.; Fedorchuk, Nicholas D.; Ives, Libby R.W.; McNall, Natalie B.; Litwin, Scott A.; Borucki, Mark K.; Malone, John E.; Kusick, Allison R. (Earth-Science Reviews, 2021)
The late Paleozoic Ice Age (LPIA) was one of Earth's most important Phanerozoic climatic events lasting for over 100 Mys. Despite its importance, its history is controversial with two hypotheses that portray glaciation differently (Fig. 1). Traditional views characterize the LPIA as a continuous glacial event that lasted from the Middle Mississippian until the Late Permian with a massive ice sheet that covered Gondwana throughout this interval. This approach often uses only one or two proxies to define the glaciation. The other emerging hypothesis suggests that numerous ice sheets occurred in Gondwana with individual glacial events lasting up to 10 Mys alternating with glacial minima/non-glacial intervals of similar duration. Both views are still prevalent. Both near- and far-field proxies are used to define the ice age. Near-field proxies include the occurrence/absence of diamictites, glaciotectonic deposits/landforms, striated clasts and clast pavements, outsized clasts (dropstones), rhythmites, cyclic diamictite-bearing successions, glendonites, grooved and striated surfaces, streamline landforms, and U-shaped paleovalleys. Detrital zircons and chemical index of alteration (CIA) studies help to delineate the occurrence, extent, and location of glaciation. Multiple complexities occur with the use of these proxies as different non-glacial processes and driving factors can produce similar features or results. Far-field proxies focus on identifying changes in eustacy. These include the occurrence of cyclic successions composed of alternating nonmarine and marine strata (cyclothems), depth of incised valleys, paleotopographic relief, phosphatic black shales, and changing oxygen isotope ratios. Like the near-field record, far-field proxies are complex indicators with varied nuances that make their application challenging. Here we discuss the limitations and use of these proxies and promote a multiproxy approach to investigating Earth's glacial intervals. We suggest that studies incorporate multiple proxies coupled with detailed environmental, paleoflow, and paleogeographic analyses to better constrain the occurrence, timing, and extent of glaciation and its influence on global systems. This approach will provide a robust view of the LPIA. We also consider the magnitude and nature of sea-level response to changing ice volumes by discussing ice-volume fluctuations, basin subsidence's modification of glacioeustacy, and sea-level's response to global isostatic adjustment (GIA). In considering these features, it becomes apparent that glacioeustacy is more complex than previously envisioned. © 2021 Elsevier B.V.
Keywords: Gondwana; Mississippian; Paleozoic; Pleistocene; dept.esc; glaciation; glacioeustacy; ice sheet; peer-reviewed